Improving Senior Knowledge Management in Ageing Societies: The Bakuntza Project (Journal of Advanced Research in Social Sciences, 2019)
The growing emergence of knowledge-based organizations, in which knowledge is the main competitive capital of companies, makes the management of senior talent an urgent challenge to address. Arising from the increase in aging societies, the current lack of strategy-oriented to give value to age management and senior knowledge transfer within enterprises has become a priority. The Bakuntza Project (The Alliance Project) has the purpose of designing a learning mechanism that Gipuzkoa´s companies can utilize in order to capture the knowledge obtained from senior workers and retain it to transfer back into society. It is a research-action initiative that is promoted within the framework of Etorkizuna Eraikiz (Building the Future) which is a collaborative governance initiative led by the Provincial Council of Gipuzkoa (Basque Country, Spain). The methodology is based on a process of activation of senior knowledge within companies, so that, by training through active experimentation, entrepreneurial projects are generated within companies. Understanding and managing the senior knowledge transfer process in organizations as a global challenge is essential to enhance the territory´s competitiveness. The Bakuntza Project’s value is that it brings together, within the framework of a synergic and structured process, the entrepreneurial activity of unemployed youth and the age management processes of the companies based on an approach of creating social value.